2019
DOI: 10.1515/jogs-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Mass variation observing system by high low inter-satellite links (MOBILE) – a new concept for sustained observation of mass transport from space

Abstract: As changes in gravity are directly related to mass variability, satellite missions observing the Earth’s time varying gravity field are a unique tool for observing mass transport processes in the Earth system, such as the water cycle, rapid changes in the cryosphere, oceans, and solid Earth processes, on a global scale. The observation of Earth’s gravity field was successfully performed by the GRACE and GOCE satellite missions, and will be continued by the GRACE Follow-On mission. A comprehensive team of Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It can be shown that with such a configuration temporal aliasing effects, which are one of the dominant error contributors of singlepair missions like GRACE and GRACE-FO and result in typical striping patterns, can be reduced significantly (in the order of a factor 5 to 10; Wiese et al, 2011, Daras andPail, 2017). Another promising constellation is high-precision high-low tracking between high or medium orbiting and low orbiting satellites (Hauk et al, 2017), a concept which has been proposed to the European Space Agency (ESA) in response to the Earth Explorer 10 call (Pail et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that with such a configuration temporal aliasing effects, which are one of the dominant error contributors of singlepair missions like GRACE and GRACE-FO and result in typical striping patterns, can be reduced significantly (in the order of a factor 5 to 10; Wiese et al, 2011, Daras andPail, 2017). Another promising constellation is high-precision high-low tracking between high or medium orbiting and low orbiting satellites (Hauk et al, 2017), a concept which has been proposed to the European Space Agency (ESA) in response to the Earth Explorer 10 call (Pail et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, in 2016 e.motion 2 was proposed as ESA Earth Explorer 9 mission [10]. Another innovative observation concept is high-precision high-low inter-satellite ranging, which was proposed as the MOBILE mission in response to ESA's Earth Explorer 10 call, e.g., [11] and [12]. On US side, the United States National Academies of Sciences, Engineering, and Medicine published the decadal strategy for Earth observation from space [13], where mass change was identified as one of the top five designated observables to be implemented by future US Earth observation missions, in order to ensure continuity and enable long-term mass budget analyses of the Earth system.…”
Section: Introductionmentioning
confidence: 99%
“…Also, ESA launched a feasibility study on NGGM with the use of Laser interferometer for ranging measurements (Dionisio et al 2018). A NGGM based on the innovative observational concept of a high-low tracking formation with micrometre ranging accuracy (Pail et al 2019) is currently being studied by CNES. Eventually also, the reversing of GNSS-based kinematic trajectories of low-Earth-orbit constellations might be able to monitor groundwater evolution (e.g., Bezděk et al 2016 and references therein).…”
Section: Future Of Gravimetry Missionsmentioning
confidence: 99%